Analysis of the nutritional status and eating habits of a group of pregnant women in Londrina, Paraná - Farias, Camila Beneli; Bandoni, Isabela Vicente; Santos, Graziela Maria Gorla Campiolo dos (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No especial (2022): Nutrição, 2022)
Pregnancy is a period marked by intense changes in the maternal organism.  Nutritional status and food consumption are related to the pregnancy prognosis.  Therefore, the aim of this study was to evaluate the pre-pregnancy nutritional status,  gestational weight gain, gestational nutritional status and food consumption of a  group of pregnant women in Londrina, Paraná. This study was a cross-sectional, descriptive and quantitative research. Sociodemographic variables, anthropometric  and gestational data were collected. Food consumption was assessed using a Food  Frequency Questionnaire (FFQ). Pre-gestational and current nutritional status and  weight gain were evaluated as recommended by the Ministry of Health. Spearman's  correlation was applied in the data analysis. Results: Most pregnant women had  adequate nutritional status before pregnancy, but due to inappropriate weight gain,  they evolved with inadequate current nutritional status. There was a statistical  correlation between pre-pregnancy and current nutritional status and weight gain.  From the results, it is concluded that knowing the nutritional profile presented by  pregnant women is extremely important to identify gestational risk factors and assist  in the development of strategies aimed at nutritional care during pregnancy.